Background/Objectives: The purpose of this study was to investigate the effects of 8 weeks of combined exercise on blood lipid and obesity-related hormones in postmenopausal women and to provide basic data in regard to exercise prescription for effective - Kim, Do-Jin; Kim, Jong-Hyuck (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to investigate the effects of 8 weeks of combined exercise on blood lipid and obesity-related hormones in postmenopausal women and to provide basic data in regard to exercise prescription for effective postmenopausal women’s health management. Methods/Statistical analysis: The subjects of this study were postmenopausal women living in Seoul, Korea. The combined exercise of the experimental group consisted of treadmill walking and weight training using weight. The exercise intensity was able to maintain the exercise intensity of 60%-70% or more based on RPE and 1RM. Exercise intensity was adjusted in units of 4 weeks. 60 minutes four times a week for 8 weeks. Warm- up and cool down were conducted for 10 minutes each. The exercise was conducted for 20 minutes of aerobic exercise and 20 minutes of resistance exercise. In the data processing, descriptive statistics were presented for each measurement item and a 2-way RGRM ANOVA was conducted to examine the interaction effects between groups. Findings: The results have shown significant interaction effects in the blood lipids(TG, TC, HLD-C, LDL-C) and the obesity-related hormones(Leptin, adiponectic). Improvements/Applications: The purpose of this study was to investigate the effects of resistance exercise using treadmill and weight on blood lipid and obesity-related hormone in postmenopausal women. The results suggest that combined exercise has a positive effect on blood lipid and obesity-related hormones. Therefore, the 8-week combined exercise program proved that obesity and cardiovascular disease can be prevented and improved by effectively improving blood lipid and obesity-related hormones. Considering these aspects, it is necessary to develop various combined exercise programs for postmenopausal women.